2009
DOI: 10.5424/fs/2009183-01074
|View full text |Cite
|
Sign up to set email alerts
|

The amount of coarse dead wood and associated decay rates in forest reserves and managed forests, northwest Turkey

Abstract: This study describes the state of coarse dead wood (CDW) in the Forest Reserve and the Managed Forest zones of northern conifer-broadleaved mixed forest. The results showed mean total CDW volumes in the ranges 30,05±11,06 m 3 /ha in the Forest Reserve (6,33±2,98% of the LW volume), and 9,31±2,84 m 3 /ha in the Managed Forest (1,96±0,84% of the LW volume). The total CDW volume was 3,22 times higher in the Forest Reserve than in the Managed Forest.The CDW log1 and CDW snag1 were the most abundant CDW decay class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As a result of the ecological difficulties in the high altitudes, more deadwood are left in the forests where regeneration difficulties are also experienced in these zones, where the cohorts can form more intensively and strongly. Colak et al (2009) described the state of coarse dead wood (CDW) in the managed forest of northern conifer-broadleaved mixed forest. The results of their research showed mean total CDW volumes 9.31±2.84 m 3 /ha in the managed forest.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the ecological difficulties in the high altitudes, more deadwood are left in the forests where regeneration difficulties are also experienced in these zones, where the cohorts can form more intensively and strongly. Colak et al (2009) described the state of coarse dead wood (CDW) in the managed forest of northern conifer-broadleaved mixed forest. The results of their research showed mean total CDW volumes 9.31±2.84 m 3 /ha in the managed forest.…”
Section: Discussionmentioning
confidence: 99%
“…It can provide all kinds of habitats and growth resources for organisms 8 . A vast number of academics have investigated dead wood reserves in forest ecosystems [9][10][11][12][13] . Many research are now being conducted on the changes in nutritional components throughout the decomposition process of dead wood.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, studies to determine carbon stocks of woody debris are still inadequate [20]. The number of woody debris studies is also very limited in Turkey [21][22][23]. Woody debris is important for carbon and one of the major carbon pools that should be calculated in the preparation of national inventories of greenhouse gases [24,25].…”
Section: Introductionmentioning
confidence: 99%